The Study of Changing Anchor from Launching Model to Hanging Model on Barge Ship Owned by P.T. X - Faturachman, Danny; Djaeni, Achmad; Fridolini, (International Journal of Marine Engineering Innovation and Research, 2025)
Anchor is a device for tethering a ship to the bottom of the water, in the sea, river, or lake, so that it does not move from place to place due to gusts of wind, current, or waves. Anchors are heavy equipment that is dropped to the seabed from a ship or boat to maintain its position so that it does not drift. PT X has several tug boats, small vessels whose function is to pull or push large ships in port. In addition, this ship also functions to pull barges filled with coal from the coal processing plant to be brought to the port, where the coal is unloaded to be carried by transport trucks. On these barges, damage to the anchor machine often occurs, especially the teeth on the gear-box, axle pulleys (pulleys), the main shaft of the main-gear (main gear), the gear-box casing, the teeth on the main-gear and others which have been sufficient so far. Interfere with operations, and the ship becomes idle. For this reason, this research was conducted to study the change in the anchor system from the glide model to a new system in the hanging model, in order to reduce the use of anchor winch power and avoid damage to the gear-box and anchor engine.